Let f ( x ) be a real valued function defined on x ∈ R , x = 0 , 1 such that for all real values of x , f ( x ) + f ( x x − 1 ) = x 1 . f ( − 4 ) = b a , where a and b are coprime integers. What is a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice! Did the same way! Full points for that!
Let g ( x ) = x x − 1 . Some scratch-work reveals that, for x = 0 , 1 , g ( g ( g ( x ) ) ) = x . Keeping this in mind, and iteratively plugging in x , g ( x ) , g ( g ( x ) ) , for x , we get
f
(
x
)
+
f
(
g
(
x
)
)
=
x
1
,
f
(
g
(
x
)
)
+
f
(
g
(
g
(
x
)
)
)
=
g
(
x
)
1
,
f
(
g
(
g
(
x
)
)
)
+
f
(
g
(
g
(
g
(
x
)
)
)
)
=
f
(
g
(
g
(
x
)
)
)
+
f
(
x
)
=
g
(
g
(
x
)
)
1
,
where we used the identity obtained for g ( x ) in the last equation. Since we can calculate x 1 , g ( x ) 1 , and g ( g ( x ) ) 1 , the three equations above give us linear system of equations for f ( x ) , f ( g ( x ) ) , and f ( g ( g ( x ) ) ) . Adding the first and third equations and then subtracting the second gives us 2 f ( x ) = x 1 + g ( g ( x ) ) 1 − g ( x ) 1 ⇒ f ( x ) = 2 1 ( x 1 + g ( g ( x ) ) 1 − g ( x ) 1 ) . Plugging in x = − 4 yields f ( − 4 ) = 4 0 7 9 = b a . 7 9 = a and 4 0 = b are coprime, giving us the answer a + b = 7 9 + 4 0 = 1 1 9 .
This solution shows how to calculate f ( x ) for any value of x = 0 , 1 .
Log in to reply
Love this problem. Nice job Calvin and Daniel! :D
We are given f ( x ) + f ( x x − 1 ) = x 1 . (1)
We substitute x x − 1 into x in (1) to get:
f ( x x − 1 ) + f ( x x − 1 x x − 1 − 1 ) = x x − 1 1 , or
f ( x x − 1 ) + f ( 1 − x 1 ) = x − 1 x . (2)
Now we substitute 1 − x 1 into x in (1) to get:
f ( 1 − x 1 ) + f ( 1 − x 1 1 − x 1 − 1 ) = 1 − x 1 1 , or
f ( 1 − x 1 ) + f ( x ) = 1 − x . (3)
By subtracting (2) from (1), we have:
f ( x ) − f ( 1 − x 1 ) = x ( 1 − x ) x 2 − x + 1 . (4)
We then add (3) and (4) to have:
2 f ( x ) = x ( 1 − x ) x 2 − x + 1 + ( 1 − x ) , or
f ( x ) = 2 x ( 1 − x ) x 3 − x 2 + 1 .
Hence, f ( − 4 ) = 4 0 7 9 , and 7 9 + 4 0 = 1 1 9 .
*We can also solve for f ( − 4 ) without using the system of 3 functional equations by substituting − 4 in x . We'll get f ( − 4 ) + f ( 4 5 ) = − 4 1 . Then we substitute 4 5 in x to get f ( 4 5 ) + f ( 5 1 ) = 5 4 . Finally we substitute 5 1 in x to get f ( 5 1 ) + f ( − 4 ) = 5 and solve the system of equations for f ( − 4 ) .
Exactly what I did!!
when we substitute values of x = -4 , 1/5 , 5/4, we get three equations with three unknowns and then we can solve easily for f(-4).
We remark that f ( x ) + f ( 1 − x 1 ) = x 1 inspires us to consider g ( x ) = 1 − x 1 , which is well-known to satisfy g ( g ( g ( x ) ) ) = x . While we admit that knowing this fact helps inspire the solution, it is not difficult to quickly to show this property. The original equation becomes f ( x ) + f ( g ( x ) ) = x 1 . Now, take s , t ∈ R such that g ( s ) = x and g ( g ( t ) ) = x . Making use of our original identity, g ( g ( g ( x ) ) ) = x , this function must also satisfy f ( g ( x ) ) + f ( g ( g ( x ) ) ) = g ( x ) 1 and f ( g ( g ( x ) ) ) + f ( x ) = g ( g ( x ) ) 1 . We have three equations, from which we can isolate f ( x ) as f ( x ) = 2 x 1 − g ( x ) 1 + g ( g ( x ) ) 1 . Then, we simply substitute x = − 4 , and after some algebra, we arrive at f ( − 4 ) = 2 − 4 1 − 5 / 4 1 + 1 / 5 1 = 4 0 7 9 so a + b = 1 1 9 .
x = -4, so f(-4) + f(5/4) = -1/4, x = 5/4, f(5/4) + f(1/5) = 4/5, so f(-4) - f(1/5) = -21/20. x = 1/5, f(1/5) + f(-4) = 5, elimination of f(1/5),we get 2f(-4) = 79/20 So the answer f(-4) = 79/40, and a + b = 79 + 40 = 119
notice that f(1/5) + f(-4) = 5 - (1) f(5/4) + f(1/5) = 4/5 - (2) f(-4) + f(5/4) = -1/4 - (3) (1) - (2), we get f(-4) - f(5/4) = 21/5 - (4) (3) + (4), 2f(-4) = 79/20 f(-4) = 79/40 f (-4) = 79+40 = 119
when x = 1/5, f(1/5) + f(-4) = 5 when x= 5/4, f(5/4) + f(1/5) = 4/5. when x= -4, f(-4) + f(5/4) = -1/4, there are three unknowns and three equations, we can solve them to get, f(-4) = 79/40... therefore a + b = 79 + 40 = 119
f(x)+f(x-1/x)=1/x put x=-4 in the above equation we get f(-4)+f(5/4)=-1/4 (eqn1) put x=5/4 we get f(5/4)+f(1/5)=4/5 (eqn2) put x=1/5 we get f(1/5)+f(-4)=5 (eqn 3) now,subtract eqn2 from eqn3 and then add with eqn1. then we get 2 f(-4)=5-4/5-1/4 f(-4)=79/40 a=79,b=40 thus a+b=119
f(-4)+f(5/4)=-1/4 f(5/4)+f(1/5)=4/5 f(1/5)+f(-4)=5 f(-4)=(5-1/4-4/5)/2=79/40
x = -4
f(-4) + f(5/4) = -1/4 .....(1)
x = 5/4
f(5/4) + f(1/5) = 4/5 .....(2)
x = 1/5
f(1/5) + f(-4) = 5 ..........(3)
From 1,2 and 3
f(-4)= a/b = 79/40
So, a+b = 119
If we put x = − 4 in the text, we obtain f ( − 4 ) = − 4 1 − f ( − 4 − 4 − 1 ) = − 4 1 − f ( 4 5 ) Puttin again x = 4 5 in the text, we have f ( 4 5 ) = 4 5 1 − f ( 4 5 4 5 − 1 ) = 5 4 − f ( 5 1 ) Again, setting x = 5 1 in the text we obtain f ( 5 1 ) = 5 1 1 − f ( 5 1 5 1 − 1 ) = 5 − f ( − 4 ) So f ( − 4 ) = − 4 1 − f ( 4 5 ) = = − 4 1 − ( 5 4 − f ( 5 1 ) ) = = − 4 1 − ( 5 4 − ( 5 − f ( − 4 ) ) ) that is 2 f ( − 4 ) = 5 − 4 1 − 5 4 = 2 0 1 0 0 − 5 − 1 6 = 2 0 7 9 Hence we have f ( − 4 ) = 4 0 7 9 and a + b = 7 9 + 4 0 = 1 1 9 .
Given: f(x) + f(1-\frac {1}{x}) = \frac {1}{x} Putting x = -4 : f(-4) + f(\frac {5}{4}) = -(\frac {1}{4})..................(i) Putting x= \frac {5}{4} : f(\frac {5}{4}) + f(\frac {1}{5}) = \frac {4}{5}....................(ii) Putting x = \frac {1}{5} : f(\frac {1}{5}) + f(-4) = 5....................(iii) equ (ii) - equ (i) : f(\frac {1}{5}) - f(-4) = \frac {21}{20}..................(iv) equ (iii) - equ (iv) : 2f(-4) = 5 - \frac {21}{20} = \frac {79}{20} => f(-4) = \frac {79}{40} = \frac {a}{b} => a + b = 119
Letting x = − 4 , 5 4 , 5 1 gives the following equations, respectively:
f ( − 4 ) + f ( 4 5 ) = 4 − 1 .
f ( 4 5 ) + f ( 5 1 ) = 5 4 .
f ( 5 1 ) + f ( − 4 ) = 5 .
Adding the three equation together, we get
2 ( f ( − 4 ) + f ( 4 5 ) + f ( 5 1 ) ) = 2 0 1 1 1 .
We divide both sides by 2 to get
f ( − 4 ) + f ( 4 5 ) + f ( 5 1 ) = 4 0 1 1 1 .
Subtracting this equation by the second equation from above thus yields
f ( − 4 ) = 4 0 1 1 1 − 5 4 = 4 0 7 9 .
Our desired answer is 7 9 + 4 0 = 1 1 9 .
Substitute x = − 4 , 4 5 and 5 1 .
f ( − 4 ) + f ( − 4 − 4 − 1 ) = − 4 1
When simplified: f ( − 4 ) + f ( 4 5 ) = − 4 1
f ( 4 5 ) + f ( 4 5 4 5 − 1 ) = 5 4
When simplified: f ( 4 5 ) + f ( 5 1 ) = 5 4
f ( 5 1 ) + f ( 5 1 5 1 − 1 ) = 5
When simplified: f ( 5 1 ) + f ( − 4 ) = 5
Adding the 3 simplified equations, we get:
2 f ( − 4 ) + 2 f ( 4 5 ) + 2 f ( 5 1 ) = − 4 1 + 5 4 + 5 = 2 0 1 1 1
Dividing by 2, we get:
f ( − 4 ) + f ( 4 5 ) + f ( 5 1 ) = 4 0 1 1 1
Subtracting f ( 4 5 ) + f ( 5 1 ) = 5 4 , we get:
f ( − 4 ) = 4 0 1 1 1 − 5 4 = 4 0 7 9
Hence a + b = 7 9 + 4 0 = 1 1 9 .
f(-4)=f(-4)+f( 4 5 )= 4 − 1 --------------------------------[ 1 ]
f( 4 5 )=f( 4 5 )+f( 5 1 )= 5 4
f( 5 1 )=f( 5 1 )+f( − 4 )= 5
f( 5 1 )= 5 -f( − 4 )
f( 4 5 )+ 5 -f( − 4 )= 5 4
f( 4 5 )= 5 − 2 1 +f( − 4 )
Putting value of f( 4 5 ) in equation [ 1 ]
we get
f( − 4 )+f( − 4 )- 5 − 2 1 = 4 − 1
On solving we get
f( − 4 )= 4 0 7 9
Thus a = 7 9 a n d b = 4 0
thus a + b = 1 1 9
We see that setting x = − 4 , f ( − 4 ) + f ( 4 5 ) = 4 − 1 − − − ( i )
setting x = 4 5 , f ( 4 5 ) + f ( 5 1 ) = 5 − − − ( i i )
setting x = 5 1 , f ( 5 1 ) + f ( − 4 ) = 5 − − − ( i i i ) .
Now , ( i ) − ( i i ) + ( i i i ) gives f ( − 4 ) = 4 0 7 9 = b a .
Thus our required answer is a + b = 7 9 + 4 0 = 1 1 9 .
Thats what I did. But will it apply to all questions of this type?
first, we look at the function f( \frac {x-1}{x} ). we can see that it's equal to f( 1- \frac {1}{x} )
we put x= -4 then f(-4) + f(1 - /frac {1}{-4}) = /frac {1}{-4}
then f(-4) + f(/frac {5}{4} ) = /frac {-1}{4}
by applying the functiun to x= /frac {5}{4}
we have: f(/frac {5}{4}) + f( /frac {1}{5}) = /frac {4}{5}
and by applying it to x= /frac {1}{5}
we have f( /frac {1}{5}) + f(-4)= 5 thus, we have 3 different functions and 3 equations, so we put:
x= f(-4)
y= /frac {5}{4}
z= /frac {1}{5}
we get
x+y= /frac {-1}{4}
y+z= /frac {4}{5}
z+x= 5
by using the 3rd equality we have : z= 5-x
by replacing it in the second equality we get:
y+5-x= /frac {4}{5}
thus y-x= /frac {-21}{5}
and we have: x+y= /frac {-1}{4}
by adding them side by side we get
2y= /frac {1}{4} +/frac {-21}{5}
2y= /frac {-89}{20}
so y= /frac{-89}{40}
and we have: x+y= /frac {-1}{4}
then x= /frac {-1}{4} - /frac{-89}{40}
x= /frac{79}{40} then f(-4) = /frac{79}{40}
since 79 and 40 are coprime, and f(-4)= /frac{a}{b} where a and b are coprime, then a=79 and b=40, thus a+b=79+40=119
Given ; f ( x ) + f ( x x − 1 ) = x 1 . . . ( 1 ) .Make the transformation x → 1 − x 1 Now we will get
f ( 1 − x 1 ) + f ( 1 − x 1 ) = x − 1 x . . . ( 2 )
Again make the transformation x → 1 − x 1 We will get
f ( 1 − x 1 ) + f ( x ) = 1 − x . . . ( 3 )
( 1 ) − ( 2 ) + ( 3 ) gives,
f ( x ) = 2 x ( 1 − x ) x 3 − x 2 + 1
Problem Loading...
Note Loading...
Set Loading...
One can do this the general way, or just plug in -4. I'll do both here. f ( − 4 ) + f ( ( − 4 ) ( − 4 ) − 1 ) = ( − 4 ) 1 or f ( − 4 ) + f ( 4 5 ) = − 4 1
f ( 4 5 ) + f ( 4 5 4 5 − 1 ) = 4 5 1 or f ( 4 5 ) + f ( 5 1 ) = 5 4
f ( 5 1 ) + f ( 5 1 5 1 − 1 ) = 5 1 1 , or f ( 5 1 ) + f ( − 4 ) = 5
f ( − 4 ) + f ( 4 5 ) + f ( 5 1 ) + f ( − 4 ) = 5 + ( − 4 1 )
2 f ( − 4 ) + f ( 4 5 ) + f ( 5 1 ) = 4 1 9 But f ( 4 5 ) + f ( 5 1 ) = 5 4 , so
2 f ( − 4 ) + 5 4 = 4 1 9
f ( − 4 ) = 4 0 7 9 , and since g c d ( 7 9 , 4 0 ) = 1 , they are coprime, and b a = 4 0 7 9 ⇒ a + b = 7 9 + 4 0 = 1 1 9
This is the general method, where we solve for f(x): f ( x ) + f ( x x − 1 ) = x 1 . Let this equation be ( A ) . Then,
f ( x x − 1 ) + f ( x x − 1 x x − 1 − 1 ) = x x − 1 1 , or f ( x x − 1 ) + f ( 1 − x 1 ) = x − 1 x Let this equation be ( B ) . The last iteration will be:
f ( 1 − x 1 ) + f ( 1 − x 1 1 − x 1 − 1 ) = 1 − x 1 1 , or f ( 1 − x 1 ) + f ( x ) = 1 − x Let this be equation ( C ) . Now add equations ( A ) and ( C ) .
f ( x ) + f ( x x − 1 ) + f ( 1 − x 1 ) + f ( x ) = x 1 + 1 − x
2 f ( x ) + f ( x x − 1 ) + f ( 1 − x 1 ) = x x + 1 Now, substitute the two last terms on the right side using ( B ) :
2 f ( x ) + x − 1 x = x x + 1 With a little algebra, we get
f ( x ) = 2 x ( 1 − x ) x 3 − x 2 + 1 , and
f ( − 4 ) = 2 ( − 4 ) ( 1 − ( − 4 ) ) ( − 4 ) 3 − ( − 4 ) 2 + 1 = 4 0 7 9